Baby Brains at work. (2nd March 2020) - Harries, Judith
Abstract : Award-winning author and illustrator Simon James is renowned for his books featuring Baby Brains, the extraordinarily smart baby. They can be used as a springboard for children to write letters, cards, lists and labels and experiment with rhyming words.